Observaciones sobre el comportamiento sexual del escarabajo de la hoja de los cereales, Oulema melanopus (L) (Coleoptera: Chrysomelidae) - Merino M, G. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
A laboratory research project was conducted to investigate the sexual behavior of Oulema melanopus (L). The work was carried out in two steps: the first consisted of careful daily observations of individuals in populations of 20 insects confined in small cages over barley seedlings, the second consisted of daily observations of 20 isolated couples captured in their first or one of their early copulations. Courtship prior to mating has not been established. The time of actual copulation ranged from 4 to 121 minutes. A maximum of 3 copulations a day and a total of 23 calculations in 17 days was verified in two different couples, respectively, with 3 daily observations. A conspicuous drop of copulatory fluid that usually acquire considerable size was characteristic of copulation. There was frequently a time lapse between the end of copulation and separation and also a varied time between mounting and copulation. Mounting without copulation and interruptions of intercourse were common. Definite homosexual behavior in the male of this species was observed during this study